2020
DOI: 10.3892/etm.2020.9182
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of asiatic acid on autophagy in myocardial ischemia‑reperfusion injury <em>in&nbsp;vivo</em> and <em>in&nbsp;vitro</em>

Abstract: Myocardial ischemia-reperfusion injury (MIRI) is a major cause of heart failure in patients with coronary heart disease. The excessive accumulation of reactive oxygen species (ROS) during MIRI induces the overactivation of an autophagic response, which aggravates myocardial cell damage. Asiatic acid (AA) is a triterpenoid compound, which is extracted from Centella asiatica and exhibits a variety of pharmacological effects such as hepatoprotective, neuroprotective and antioxidant. However, the association of AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…As a traditional Chinese medicine, AA exerts beneficial effects on oxidative stress in many disease models. In our previous study, we found that AA reduced ROS generation during MIRI and inhibited excess autophagy [ 18 ]. The results of the current study suggest that oxidative stress-induced injury plays a significant role in MIRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a traditional Chinese medicine, AA exerts beneficial effects on oxidative stress in many disease models. In our previous study, we found that AA reduced ROS generation during MIRI and inhibited excess autophagy [ 18 ]. The results of the current study suggest that oxidative stress-induced injury plays a significant role in MIRI.…”
Section: Discussionmentioning
confidence: 99%
“…In a hepatic I-R injury model, the protective effect of AA was achieved by increasing the expression of peroxisome proliferator-activated receptor gamma (PPAR γ ) and ultimately attenuating the activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome [ 17 ]. Pharmacological studies of AA in MIRI have also been documented [ 18 , 19 ], but its mechanism remains ambiguous. In the current study, we combined in vivo and in vitro models to explore additional mechanisms of AA during MIRI and aimed to prove the potential pharmacological properties of AA in the clinical treatment of CHD.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that Beclin-1-mediated autophagy is not only regulated by its own expression, but is also promoted by the binding of Beclin-1 and Bcl-2 ( Marquez and Xu, 2012 ). Previous studies have shown that the balance between Bcl-2 and Beclin-1 protein expression affects the levels of autophagy ( Yi et al, 2020 ). We therefore explored the association between Bcl-2 and Beclin-1 protein expression in the crosstalk between apoptosis and autophagy in rat heart after I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Skin stimulation agents, including LPS, TNF-α, or DNCB, act as irritants to keratinocytes, and these stimulated keratinocytes, in turn, activate the MAPK, Akt, and NF-κB signaling pathways [ 36 ]. The p -p38 pathway is more responsive to oxidative stress than other MAPK signaling pathways (such as p-ERK and p-JNK) [ 37 ], and the p -p38 pathway is involved in the chronic phase of AD pathogenesis [ 38 ]. NF-κB is a transcription factor that facilitates allergic diseases, such as AD and asthma, by increasing the levels of inflammatory cytokines [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%